Sobre esta igreja edificarei minha empresa: organizações religiosas e empreendedorismo - Serafim, Maurício Custódio (2008)
With this work I intended to approach the following research problem: In which ways do the religious organizations promote the entrepreneurship among their members and how they support the enterprising follower in Brazil? The research has the economic sociology approach and the strategy I employ in my research is a qualitative and comparative case study of two religious organizations. The first one is of the Catholic Church, called Focolare Movement. And the other one is of an Evangelical Church, locally denominated “Renascer em Cristo” (Reborn in Christ). The data were collected through observation, interviews and documental research. In general, the religious structures of the investigated organizations form a special type of social capital, denominated of spiritual capital – through closure of social networks, appropriable social organization, obligations and norms, information channels and religious networks of mutual aid – capable to create and support organizational resources, which are cultural/symbolic resources, formation, information and spiritual support/motivational spaces, and that are mobilized in a way that facilitates the entrepreneurs’ actions. These resources give relative advantages to the entrepreneurs, such as: religious technologies; psychological support; reduction of the costs of the collection and access to the information, of negotiation and of the establishment of contracts; specific information and interpreted in agreement with the religious world vision; a system of meanings that creates that world vision and sustained by the plausibility structures, giving them larger subjective degree of certainty, hope and faith concerning their businesses; services rendered technicians by members of the organization; development of the human capital due to the continuous learning through courses, seminars, lectures, and congresses; changes of experience; and possibilities of businesses, including possible partners, suppliers and customers.